Pengaruh Model Pembelajaran Kooperatif TipeBamboo DancingTerhadap Hasil Belajar pada Mata Pelajaran Komputer dan Jaringan Dasar Jurusan TKJ di SMKN 1 Kinali - Sari, Mita Purnama; Supriadi, Supriadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the current basic computer and network learning outcomes where learning outcomes are below the Completeness Criteria. Problems that are found require a problem-based learning strategy that can help teachers in the delivery of learning materials, namely by asking students to solve a problem related to the subjectmatter so that students can be active in the learning process. This study aims to determine whether there is an